EFFECTIVENESS OF WHATSAPP BOT-BASED EDUCATIONAL MEDIA AND LECTURES ON INCREASING MOTHER’S KNOWLEDGE ABOUT GASTROENTERITIS IN CHILDREN - Sonia Puspita Ar Royo; Anis Ika Nur Rohmah; Ika Rizki Anggraini; Nur Melliza (Nurse and Health)
Background: Gastroenteritis is the main cause of death in children under five years of age with symptoms of dehydration, which causes high mortality rates. Gastroenteritis risk factors include poor hygiene, unclean water supplies, and lack of parental knowledge. Providing health education regarding gastroenteritis is very important to increase mother’s knowledge. WhatsApp bot and lectures are effective media that can be used in health education.